Importance of Visual Arts in Education: A Challenge in Teacher Formation - Ramón Esteban Cárdenas-Pérez; Andrés Troncoso-Ávila (Universidad Nacional, Costa Rica, 2014)
This literature review addresses the redefinition of the Visual Arts curriculum as established by the Ministry of Education of Chile, as well as the action-reaction strategies that primary education teachers should consider when teaching different artistic skills to students grades 1 through 6. It is concluded that the proposed Visual Arts curriculum is a powerful educational tool to assist teachers to contextualize arts teaching; help students to express their ideas and emotions based on a critical, reflective, and permanent attitude; and generate opportunities for personal growth focused on the acquisition of creative skills and models of arts education which contribute, as a whole, to the development of human capacities.